Уступительность как метатекстовое явление - Bogusławski, Andrzej (Lingua Posnaniensis, 2010)
The author deals immediately with the properties of the Russian concessive word xomr. He assigns it the task of conveying the idea of the possibility of q and p (where q is directly bound with the word xomr, and p, with the rest of a given sentence), while the relevant sentence represents, primarily, knowledge that p, q is the case. But the object of his main interest is the interpretation of the status of the word, as well as of all similar units of language, in the overall structure of knowledge representation as materializing in sentences. Following the lead of Wajszczuk, he ascribes such units the property of forming a special layer of information in the sentence: the metatextual layer of the speaker's comments on his own current basic utterance. Arguments in favour of this approach are presented.